The Development of Learning Media of Islamic Education Based on Flipbook in Covid-19 Pandemic at Elementary School: Pengembangan Media Pembelajaran PAI Berbasis Flipbook Pada Masa Pandemi Covid-19 di Sekolah Dasar - MZ, Ahmad Busthomy; Syafi'i, Imam (Universitas Muhammadiyah Sidoarjo, 2021)
An Education in the 4.0 era requires teachers and students to be literate in technological developments. Conventional methods that are not relevant to technological advances must be updated. There are many teachers who have not mastered information technology in the learning process. Boredom to do learning activities that emphasize student textbooks and worksheets, ultimately have an impact on students’ enthusiasm for learning that that are less than optimal. In order to achieve the maximum learning process, one of the alternatives offered is to use learning media with the help of the Flipbook application. This study aims to determine the validity of flipbook-based learning media and to measure the practicality of flipbook-assisted learning media in overcoming boredom. This research is a research and development that uses the ADDIE model (analyzing, design, development, implementation, evaluation). Researcher Collected data by means of observations, interviews, and distributing questionnaires, then analyzed descriptively quantitatively and qualitatively. The research subjects were 30 students of grade V SDN Sumput Sidoarjo. Based on the validation test from material experts, the average value is 84% ​​which means very valid, while the media expert test is 80% with the valid category. The practicality test of the development product obtained an average score of 80% in the attractive category. The results of the study showed that the development product is in the valid and attractive category. It can be concluded that the flipbook-based PAI learning media is practical and interesting to use as learning media. Keywords: Learning Media, PAI, Flipbook